Training for Integrating Character Education into IPA Lesson Study to Improve Student Performance in HOTS in SMAN 1 Kabupaten Sigi: Pelatihan Integrasi Pendidikan Karakter dalam Pembelajaran Bidang IPA Berpola Lesson Study untuk Mengembangkan Keterampilan HOTS Siswa SMAN 1 Kabupaten Sigi - Santoso, Tri; Suherman, Suherman; Ahmar, Dewi Satria (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
This service activity aims to improve teachers' ability to integrate character education and students' HOTS thinking skills in the learning process through the preparation of learning tools and introduce the concept of learning with lesson study to teachers. This activity is carried out in the form of training and practice of making learning tools. In the delivery of the material, the teachers were provided with information about learning with lesson study, preparation of learning tools that integrate character education, and the importance of developing HOTS skills as well as the characteristics of HOTS questions. The results of the service showed that the teachers had understood and had an overview of the learning implemented with the lesson study model. The teachers have also understood that one form of integration of character education in learning tools is by practicing the Pancasila student profile as expected in the independent curriculum. Furthermore, the teachers have understood that the project activity of strengthening the Pancasila learner profile is one of the activities that can improve students' HOTS skills. Abstrak Kegiatan pengabdian ini bertujuan untuk meningkatkan kemampuan guru dalam mengintegrasikan pendidikan karakter dan keterampilan berpikir HOTS siswa dalam proses pembelajaran melalui penyusunan perangkat pembelajaran serta memperkenalkan konsep pembelajaran dengan lesson study kepada guru. Kegiatan ini dilaksanakan dalam bentuk pelatihan dan praktek pembuatan perangkat pembelajaran. Pada penyampaian materi, para guru dibekali dengan informasi tentang pembelajaran dengan lesson study, penyusunan perangkat pembelajaran yang mengintegrasikan pendidikan karakter, dan pentingnya pengembangan keterampilan HOTS serta ciri dan karakteristik soal-soal HOTS. Hasil pengabdian menunjukkan bahwa para guru telah memahami dna telah memiliki gambaran tentang pembelajaran yang dilaksanakan dengan model lesson study. Para guru juga telah memahami bahwa salah satu bentuk integrasi pendidikan karakter dalam perangkat pembelajaran adalah dengan pengamalan profil pelajar pancasila sebagaimana yang diharapkan dapa kurikulum merdeka. Selanjutnya para guru telah memahami bahwa kegiatan project penguatan profil pelajar pancasila merupakan salah satu kegiatan yang dapat meningkatkan keterampilan HOTS siswa.